Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Review: 55

Answer

The solutions are 0 and -1 and $\frac{2}{7}$.

Work Step by Step

3x(x+1)(7x-2)=0 3x=0 or x+1=0 7x-2=0 x=0 or x+1-1=0-1 7x=2 x=0 or x=-1 or x= $\frac{2}{7}$ The solutions are 0 and -1 and $\frac{2}{7}$. Check Let x=0 3x(x+1)(7x-2)=0 3*0(0+1)(7*0-2)=0 0=0 Let x=-1 3x(x+1)(7x-2)=0 3(-1)(-1+1)[7(-1)-2]= -3*0[7(-1)-2]= 0=0 Let x=$\frac{2}{7}$ 3x(x+1)(7x-2)=0 3$\frac{2}{7}$($\frac{2}{7}$+1)(7*$\frac{2}{7}$-2)=0 3$\frac{2}{7}$($\frac{2}{7}$+1)(2-2)=0 0=0
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.